Clinico-Epidemiological Profile of Central Line-Associated Blood Stream Infections and Associated Morbidities among Patients in a Tertiary Care Hospital, Bangalore - K S Sarala; BS Nanda Kumar; V Narendranath (Medsci Publications, 2017)
Background: Central line-associated bloodstream infection (CLABSI) is often a complication of the presence of indwelling medical devices. These Central line catheters provide long-term venous access for treatment, delivery of medications and blood testing. Use of Central venous Catheters lead to bloodstream infection often referred as Central line-Associated bloodstream infection. Methods and Materials: Cross sectional retrospective data was collected among all the inpatients for the year 2015 covering 30, 954 inpatients. Data was collected as per ICD - 10 coding, analyzed using SPSS softwareOR17, interpreted and represented in the graph. Results: Prevalence rate of CLABSI was 7/1000 population, High prevalence was seen among males 144 (65.7%),Mean age ± 40.6, Average length of stay increased to 11.7 days, patients admitted to ICU complex suffered more compared to ward category, Medical related diseases contributed to 132 (60.2%) and Respiratory organ system related diseases contributed to 96(25.5%) Conclusions: Patients with Central line -associated bloodstream infection had significantly longer hospital lengths of stay; Bloodstream infections are associated with a high rate of morbidity and mortality. In this context understanding the profile, demographic variables and associated morbidity becomes an important for prevalence of the diseases.